The Cognitive Infrastructure of Opportunity Emergence - Krueger, Norris F. (Entrepreneurship Theory and Practice, 2000)
Before we can act on opportunities we must first identify those opportunities. Understanding what promotes or inhibits entrepreneurial activity thus requires understanding how we construct perceived opportunities. Seeing a prospective course of action as a credible opportunity reflects an intentions-driven process driven by known critical antecedents. Based on well-developed theory and robust empirical evidence, we propose an intentions-based model of the cognitive infrastructure that supports or inhibits how we perceive opportunities. We discuss how this model both integrates past findings and guides future research. We also show the practical diagnostic power this model offers to managers.